STRATEGI PENINGKATAN KESEJAHTERAAN SOSIAL PENYANDANG DISABILITAS NETRA MELALUI KEBIJAKAN INGKLUSIF - Ajie Hanif Muzaqi; M. Rizki Pratama; Sugeng Widodo (Journal Publicuho, 2020)
This study aims to determine strategies for improving the social welfare of persons with visual impairments through an inclusive policy implemented by the Malang Blind Social Rehabilitation Technical Implementation Unit (UPT RSCN) Malang as a forum for finding policy forms from the efforts made by the East Java Provincial Government.The research method used a qualitative approach. The data analysis used to determine the research results used descriptive analysis with an interactive data analysis model. the next process is to identify strengths, weaknesses, opportunities, and threats (SWOT) for the formulation of strategic plans in the context of community empowerment in local government institutions.The results showed that the strategies implemented in this program were passive and offensive strategies. It can be said that the implementation of the program implemented is quite good, seen from the patient's way of thinking who is more visionary, has work skills and has creativity. In addition, all patients who have been rehabilitated can compete in the world of work and have their own business for their survival. Thus, they can improve regional welfare and reduce unemployment.